The Role of TNI (Indonesian National Army) in Countering Trans-national Crimes - Imam Subandi; Muhammad Syauqillah; Sapto Priyanto; Zora A. Sukabdi; Muhamad Rum (Green Publisher Indonesia, 2024)
The involvement of the Indonesian Army in law enforcement is often a problematic issue in the context of countries that implement a democratic system. History has proven that authoritarianism is not only the domination of the military, but also the domination of every government regime including civilians that do not implement checks and balances system in the execution of the government. This is what should be the focus of the problem. Apart from that, law enforcement authority actually is not only limited to the area of civil authority which is only given to the police as a representation of state authority which obtains authority from law, but rather to the police functions in general which can also be given to the military which functions as law enforcement officers (law enforcement officials) as explained in the UN Code of Conduct for Law Enforcement as follows;